Critical Cultural Awareness: Should Vietnamese Culture Be Taught In A Different Way? - Do, Nhu Quynh (H. : ĐHQGHN, 2020)
Critical cultural awareness – the key component in the framework of intercultural communicative competence of Byram (1997) – highlights the importance of training critical thinking skills for foreign language learners. Much research has been conducted on how critical cultural awareness can be developed in language classrooms, yet very few takes classroom of native culture as a fertile context for raising such awareness. This paper is to highlight the necessity of fostering that awareness in native culture classroom. We would clarify how the conventional way of teaching Vietnamese culture at the University of Languages and International Studies is inconducive to build up critical cultural awareness for learners by critiquing the essentialism that the two course books based on and the lack of dynamic reflections of stereotypical ideas for learners via the observation of teachers and students. We then proposed some ideas to make teaching and learning practices more critical.